Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ------- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde